The Weight‐Focused Forms of Self‐Criticising/Attacking and Self‐Reassuring Scale: Confirmatory Factor Analysis and associations with control, loss of control of eating and weight in overweight and obese women. (22nd August 2018) - Duarte, Cristiana; Stubbs, James R.; Gilbert, Paul; Stalker, Carol; Catarino, Francisca; Basran, Jaskaran; Horgan, Graham; Morris, Liam
Abstract : Objectives: The Weight‐Focused Forms of Self‐Criticising/Attacking and Self‐Reassuring Scale (WFSCRS) is based on the original Forms of Self‐Criticising/Attacking and Self‐Reassuring Scale (FSCSRS; Gilbert et al., 2004, British Journal of Clinical Psychology, 43, 31) and assesses the inadequate and hated forms of self‐criticism and the ability to self‐reassure when coping with attempts to control body weight, shape, and eating. The aim of this study was to examine the factor structure, consistency, and reliability of the WFSCRS in overweight and obese women. Methods: The factorial structure of the WFSCRS was examined through a confirmatory factor analysis in 724 overweight and obese women participating in a commercial weight management programme. The scale's construct and convergent validity were also examined. Results: The WFSCRS had a three‐factor structure, similar to the FSCSRS, which fitted the data well. The WFSCRS had high internal reliability, construct, and discriminant validity. The scale was positively associated with measures of shame, body image, eating‐related difficulties, symptoms of anxiety, depression, and stress, and body mass index (BMI). The two forms of self‐criticism were significantly associated with higher BMI, and this effect was mediated by increased loss of control over eating (for both forms) and decreased flexible control over eating (for the hated self form). Conclusions: The WFSCRS is a valid measure for assessing self‐reassurance and two denigratory forms (inadequate self and hated self) of self‐criticism in people who are overweight and obese. Practitioner Points: The WFSCRS was developed to measure weight/shape and eating‐related self‐criticism and self‐reassurance. The WFSCRS was examined in a large sample of overweight and obese women attending a community‐based weight management programme. The WFSCRS presented a three‐factor structure measuring two forms of self‐criticism (inadequate self and hated self) and the ability to be self‐reassuring. The two forms of self‐criticism and self‐reassurance are differentially associated with BMI, through the mediating effect of loss of control over eating and flexible control over eating.